Comparative analysis delineates the transcriptional resistance mechanisms for pod borer resistance in the pigeonpea wild relative Cajanus scarabaeoides (L.) Thouars - Njaci, Isaac; Ngugi-Dawit, A.; Oduor, R.O.; Kago, Leah; Williams, B.; Hoang, L.T.M.; Mundree, S.G.; Ghimire, Sita R. (MDPI, 2021)
Insect pests pose a serious threat to global food production. Pod borer (Helicoverpa armigera (Hübner)) is one of the most destructive pests of leguminous crops. The use of host resistance has been an effective, environmentally friendly and sustainable approach for controlling several agricultural pests. The exploitation of natural variations in crop wild relatives could yield pest-resistant crop varieties. In this study, we used a high-throughput transcriptome profiling approach to investigate the defense mechanisms of susceptible cultivated and tolerant wild pigeonpea genotypes against H. armigera infestation. The wild genotype displayed elevated pest-induced gene expression, including the enhanced induction of phytohormone and calcium/calmodulin signaling, transcription factors, plant volatiles and secondary metabolite genes compared to the cultivated control. The biosynthetic and regulatory processes associated with flavonoids, terpenes and glucosinolate secondary metabolites showed higher accumulations in the wild genotype, suggesting the existence of distinct tolerance mechanisms. This study provides insights into the molecular mechanisms underlying insect resistance in the wild pigeonpea genotype. This information highlights the indispensable role of crop wild relatives as a source of crucial genetic resources that could be important in devising strategies for crop improvement with enhanced pest resistance.